Advances in human factors in architecture, sustainable urban planning and infrastructure : proceedings of the AHFE 2020 Virtual Conference on Human Factors in Architecture, Sustainable Urban Planning and Infrastructure, 16-20 July, 2020, USA /: proceedings of the AHFE 2020 Virtual Conference on Human Factors in Architecture, Sustainable Urban Planning and Infrastructure, 16-20 July, 2020, USA. (2020) - Unknown
No abstract available